2018
DOI: 10.1186/s40560-018-0275-y
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical outcomes of patients undergoing primary percutaneous coronary intervention for acute myocardial infarction requiring the intensive care unit

Abstract: BackgroundOutcomes for patients with ST-segment elevation myocardial infarction continue to improve, largely due to timely provision of reperfusion by primary percutaneous coronary intervention (PPCI). However, despite prompt and successful PPCI, a small proportion of patients require ventilatory and hemodynamic support in an intensive care unit (ICU). The outcome of these patients remains poorly defined.MethodsA retrospective review of all consecutive admissions post-PPCI pathway to a single ICU between Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“… 45 46 47 Secondly, most previous studies suggested increased mortality among patients admitted to an ICU, but these studies are at risk for confounding by indication and for estimating average rather than the more clinically relevant marginal treatment effects (that is, the effect on patients who could reasonably be treated in either ICU or non-ICU settings). 48 49 50 Our unadjusted and adjusted results also showed increased mortality associated with ICU admission. Other instrumental variable analyses have similarly shown a shift in the effect compared with conventional regression analyses.…”
Section: Discussionmentioning
confidence: 54%
“… 45 46 47 Secondly, most previous studies suggested increased mortality among patients admitted to an ICU, but these studies are at risk for confounding by indication and for estimating average rather than the more clinically relevant marginal treatment effects (that is, the effect on patients who could reasonably be treated in either ICU or non-ICU settings). 48 49 50 Our unadjusted and adjusted results also showed increased mortality associated with ICU admission. Other instrumental variable analyses have similarly shown a shift in the effect compared with conventional regression analyses.…”
Section: Discussionmentioning
confidence: 54%
“…In the original publication of this article [ 1 ], one author’s name was misspelling. Catherine Jaworksi should be Catherine Jaworski.…”
Section: Correctionmentioning
confidence: 99%
“…While PPCI has substantially improved the outcomes of AMI patients, the occurrence of the "no-reflow" phenomenon during the procedure remains a perplexing challenge in the field of interventional cardiology (Sunamura et al, 2017). AMI, commonly referred to as a heart attack, is a medical emergency characterized by the sudden cessation of blood flow to a portion of the heart muscle, leading to ischemia and potential myocardial damage (Dubey et al, 2017;Parhar et al, 2018). This procedure aims to salvage viable myocardium, reduce infarct size, and improve the patient's overall prognosis.…”
Section: Introductionmentioning
confidence: 99%